Neonatal neuroblastoma with adrenal primary and metastasis to the liver: A case report and a review of literature - Oladipo Omoseebi; Mosebolatan Olatokunboh Odubanjo; Olakanmi Ralph Akinde; Nzechukwu Z Ikeri; Adesoji O Ademuyiwa; Adekunle A.O. Adeyomoye (Wolters Kluwer Medknow Publications, 2016)
We report the case of a 23-day-old neonate with neuroblastoma (NBL) in the right adrenal gland and widespread metastases to the liver. This raises the possibility of foetal NBL, which was missed during periodic ultrasonography done during the mother's pregnancy. We hope that this report would increase the awareness of physicians about foetal, congenital and neonatal NBL; and of sonographers about space-occupying lesions in the foetus. The clinicopathologic features and the management of neonatal NBL are discussed.